Eksistensi Paranormal dan Penyembuh Alternatif dalam Kehidupan Masyarakat Medan - Agung Suharyanto (Universitas Negeri Medan, 2015)
The word shaman becomes one that smells negative, when it is associated with witchcraft or obscene. Many people who look skewed towards shaman because tesebut profession related to the occult and mystical. On the other hand, people do not hesitate to come to consultations even ask how to treat various diseases. Stories about the shaman becomes a very interesting thing, so many films that explore stories about them. The term shaman becomes very smelly negative, but when we see and follow the journey and their figures in various fields, they have a very religious side of life. They have many ways psychologically and ability to address various issues affecting. We also sometimes do not think with a simple appearance, they are able to survive in conditions that cornered because of the negative views of the surrounding community.